Swedish Exchange students’ alcohol use, drug use, risky sexual behaviour, mental health, and self-rated health: a follow-up study - Danehorn, Emil (Linnaeus University, 2022)
Aims: The aim of this study was to follow up on exchange students’ alcohol use, drug use, mental health, self-rated health, and risky sexual behaviour after a semester abroad and to compare them with students who remained on campus.
Methods: The study design was a follow-up study based on a previous baseline survey of 114 prospective exchange students and 451 campus students. Out of the original 565 students, 48 (42.1%) prospective exchange students and 209 (43.3%) campus students responded to the follow-up. Both the baseline survey and the follow-up survey included the General Health Questionnaire 12, one single item from Self-Rated Health, and nine items from Knowledge, Attitudes and Sexual Behaviour in Young People in Sweden.
Results: We found a statistically significant proportional increase in weekly consumption of alcohol among exchange students after their semester abroad. A larger proportion exchange student had sex with a new partner and sex with more than three partners during the last six months compared to follow-up campus students.
Conclusions: Our findings indicate that prospective exchange students consume higher amounts of alcohol, which was increased further during their semester abroad, and indulge in sexually risky behaviour to a higher degree than campus students. Exchange students increased use of alcohol and sexually risky behaviour could be associated with even greater risks due to them being in an unknown environment, unfamiliar culture and with limited support from family and friends. This highlights the need for further research on exchange students’ experiences, especially concerning alcohol use and sex while abroad.

Syftet var att följa upp utbytesstudenters alkoholanvändning, droganvändning, sexuella riskbeteende samt mentala och generella hälsa.
Svenska utbytesstudenters alkoholanvändning, droganvändning, sexuella riskbeteende och hälsa: en uppföljande studie
Keywords: exchange students; utbytesstudenter; risky sexual behaviour; sexuellt riskbeteende; Alcohol use; alkoholanvändning; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin